(untitled) (Indian Journal of Animal Production and Management, 2024)
In dairy cattle, bedding and its management contribute predominantly to the comfort of the cow, udder health and milk quality. The aim of the study is to assess the effect of different bedding materials such as concrete floor, rubber mats, coir pith and dried solid manure on hygiene and milk yield and in crossbred dairy cows. Twenty-four crossbred cows with six animals in each group were selected for the study for one lactation period spread over three different seasons. The control group (T1) was maintained in concrete floor without any bedding material. In (T2) rubber mats of 1.2 m × 1.8 m × 0.025m area were provided on concrete floor. In (T3) coir pith and (T4) dried solid manure (DSM) on concrete floor was the bedding. The mean tail head, upper rear limb, ventral abdomen, udder and lower rear limb hygiene score of the T1 group were higher than other groups, which indicated that the cows became ‘dirty’ and the T3 group had lower score than others which denoted cows were ‘very clean’ with significant difference (P<0.01) between them. The range of hygiene score in cows of T2 group revealed that the cows were ‘average to dirty’ whereas in T4 ‘clean to average’. The hygiene score of cows improved during summer season and reduced in monsoon. The cows of T1 group had the lowest overall daily milk yield (8.66 ± 0.22 kg) while the cows of T3 group had the highest yield (9.98 ± 0.30 kg).